KANDUNGAN SENYAWA AKTIF PADA JAMBLANG (Syzygium Cumini (L) Skeels SEBAGAI ANTIDIABETES: LITERATURE REVIEW ARTICLE - Himyatul Hidayah; Ermi Abriyani; Surya Amal; Reni Apria Ningsih (Jurnal Buana Farma, 2023)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia caused by defects in insulin secretion, insulin action or both. It is said diabetes mellitus if blood sugar levels exceed 150 mg/dL, where the normal limit for blood sugar is 70-150 mg/dL. Treatment with natural ingredients has low side effects if used correctly. One of the plants that has anti-diabetic activity is jamblang or often called juwet (Syzygium cumini (L.). literature was conducted using Google Scholar, Science Direct, Researchgate and PubMed which were published in 2010-2020 with keywords related to the topic "Andiabetic activity syzygium cumini, jambolanun, Eugenia Jambolan antidiabetic and active compounds". The results of a review that has been carried out on the content of active compounds in jamun (Syzygium cumini (L) Skeels as an antidiabetic indicate that the active compounds in jamun are quercetin, quercetin-3-0-glycosides, rutin, mycaminose, chalcone and stigmasterol which have the potential to as an antidiabetic.